2017
DOI: 10.1016/j.jclinepi.2017.03.011
|View full text |Cite
|
Sign up to set email alerts
|

The Dutch–Flemish PROMIS Physical Function item bank exhibited strong psychometric properties in patients with chronic pain

Abstract: The Dutch-Flemish PROMIS Physical Function item bank exhibited good psychometric properties. Development of a computer adaptive test based on the large bank is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 52 publications
(48 reference statements)
4
43
2
Order By: Relevance
“…The current study showed that the PROMIS-PF-GR had sufficient unidimensionality bi-factor analysis Omega H 0.82, ECV 0.70) This is in accordance with the original PROMIS PF developmental study as well as with three validation studies of this item bank in the Netherlands [11][12][13][14]. Unidimensionality is an important prerequisite to enable IRT-based scoring and this also makes it possible to compare T-scores of our custom short form to the original PROMIS item bank and other shorts forms.…”
Section: Discussionsupporting
confidence: 89%
“…The current study showed that the PROMIS-PF-GR had sufficient unidimensionality bi-factor analysis Omega H 0.82, ECV 0.70) This is in accordance with the original PROMIS PF developmental study as well as with three validation studies of this item bank in the Netherlands [11][12][13][14]. Unidimensionality is an important prerequisite to enable IRT-based scoring and this also makes it possible to compare T-scores of our custom short form to the original PROMIS item bank and other shorts forms.…”
Section: Discussionsupporting
confidence: 89%
“…Rose et al reported a RMSEA of about 0.08 for subsets of items from the original English PF v1.2 item bank [16]. The Dutch-Flemish PROMIS Physical Function v1.2 item bank showed a RMSEA of 0.122 [19] and 0.045 [20] in previous studies, respectively. For the Spanish population in the US, a RMSEA of 0.052 was found for the PROMIS Physical Function v1.2 item bank [53].…”
Section: Discussionmentioning
confidence: 95%
“…The first version of the Dutch-Flemish PROMIS Physical Function item bank (v1.2) contained 121 items [15][16][17]. This item bank has been validated in Dutch patients with chronic pain, patients undergoing physiotherapy, and patients with rheumatoid arthritis [18][19][20]. The PROMIS Group continued to improve the item bank, and a separate item bank for upper extremity injuries was developed, containing 46 items; the PROMIS V R Physical Function -Upper Extremity (UE) v2.0 item bank [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the assessment of the cross‐cultural validity of the measures may also have been conducted in populations other than RA and would not have been captured by our literature search. For example, the cross‐cultural validity of the PROMIS physical function bank has been examined in >1,000 Dutch patients with chronic pain, and 4 items were flagged for DIF, which negligibly impacted overall scores (34). In contrast, a Spanish translation of the PROMIS physical function item bank was tested in the US general population, revealing that 50 of the 114 items were flagged for important DIF, indicating that English‐ and Spanish‐speaking individuals with the same underlying level of physical function responded differently to these questions (35).…”
Section: Discussionmentioning
confidence: 99%